2016
DOI: 10.1038/srep31479
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-enriched miRNAs are altered in the circulation of subjects with diabetes: a pilot cross-sectional study

Abstract: The clinical presentation of diabetes sometimes overlaps, contributing to ambiguity in the diagnosis. Thus, circulating pancreatic islet-enriched microRNAs (miRNAs) might be useful biomarkers of β-cell injury/dysfunction that would allow more accurate subtyping of diabetes. We measured plasma levels of selected miRNAs in subjects with prediabetes (n = 12), type 2 diabetes (T2D, n = 31), latent autoimmune diabetes of adults (LADA, n = 6) and type 1 diabetes (T1D, n = 16) and compared them to levels in healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
128
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 26 publications
15
128
3
1
Order By: Relevance
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, both miR-34a and miR-146 may impact β-cell apoptosis (Nesca et al, 2013) and miR-146b has also been implicated in the effect of cytokines on pancreatic β-cells (Roggli et al, 2010). Seyhan et al (2016) found that both miR-34a and miR-146a are up-regulated in the circulation of patients with various forms of diabetes in comparison with healthy controls, establishing a link between those miRNAs and the development of the disease.…”
Section: Mirnas and Disallowed Genesmentioning
confidence: 89%
“…In general, JAK2, CALR and MPL are considered driver mutations, though there are elegant studies examining how acquisition order dictates phenotypic destiny. 4 Additional somatic mutations found in the disease include LNK, CBL, TET2, ASXL1, IDH1/2, IKZF1, EZH2, DNMT3A, TP53, SF3B1, SRSF2, and U2AF1, a list that is likely not exhaustive. While we await additional research on the mechanistic consequences of these aberrations, retrospective studies are already looking into the prognostic importance of mutations, or groups of mutations, in patients.…”
mentioning
confidence: 99%
“…2 Furthermore, miRNAs released into the circulation after cell death, or in extracellular vesicles, have been identified in a number of different diseases. 3,4 These circulating miRNAs can be measured in the blood, and represent promising new biomarkers for both the diagnosis of disease and the assessment of treatment responses.…”
mentioning
confidence: 99%